Philosophical Counseling in the Meaning of Polish Philosophical Counseling Association - Golecka, Aleksandra; Okoń, Korneliusz; Strzałkowski, Julian (Folia Philosophica, 2023)
In this article we present a philosophical argumentation in order to justify the definition of philosophical counseling formulated by the Polish Philosophical Counseling Association. This profession was presented as a post-modern form of dialogical counseling, based on a process of philosophizing. We consider this process both as a form of logic analysis and as a form of accompanying clients through the process of philosophizing. This can be achieved by being fully present with the clients. This presence can create a space for existential questions, for better and wider understanding of the client’s inner world discussed during session topics, and for discovering their unique life philosophy. We also present the methodology of philosophical counseling and the obligatory competences which a philosophical counselor should possess